Synthesis and characterization of carbon nanofibers grown on powdered activated carbon. - Ahmed, Yehya M.; Mamun, Abdullah Al; Jameel, Ahmad Tariq; Al-Khatib, Ma'an Fahmi Rashid; Amosa, Mutiu K; Alsaadi, Mohammed Abdul Hakim (Hindawi Publishing Corporation, 2016)
Carbon nanofibers (CNFs) were synthesized through nickel ion (Ni2+) impregnation of powdered activated carbon (PAC). Chemical Vapor Deposition (CVD) using acetylene gas, in the presence of hydrogen gas, was employed for the synthesis process. Various percentages (1, 3, 5, and 7 wt. %) of Ni2+ catalysts were used in the impregnation of Ni2+ into PAC. Field Emission Scanning Electron Microscope (FESEM), Fourier Transform Infrared (FTIR) Spectroscopy, Energy Dispersive X-Ray Analyzer (EDX), Transmission Electron Microscopy (TEM), Thermal Gravimetric Analysis (TGA), zeta potential, and Brunauer, Emmett, and Teller (BET) were utilized for the characterization of the novel composite, which possessed micro and nanodimensions. FESEM and TEM images revealed that the carbonaceous structure of the nanomaterials was fibrous instead of tubular with average width varying from 100 to 200 nanometers. The PAC surface area increased from 101 m2/g to 837 m2/g after the growth of CNF. TGA combustion temperature range was within 400°C and 570°C, while the average zeta potential of the nanocomposite materials was -24.9 mV, indicating its moderate dispersive nature in water. © 2016 Yehya M. Ahmed et al.